LABOR CONDITIONS OF THE INDIGENOUS COMMUNITIES OF THE NORORIENT NEOGRANADINO, CENTURY XVII - Pita Pico, Roger (2017)
Based on the visits made by the oidores of the Royal Audience of Santa Fe, this article aims to analyze the abuses in the working conditions imposed on the indigenous communities of the northeastern New Kingdom of Granada during the 17th century. The assignment of heavy work, the continuous extraction of their ancestral peoples, the constant pressure exerted by neighbors and encomenderos, and the commutation of the tribute for work, were factors that caused an exhausting work load through the encomienda system, the mita and the concertaje. The Spanish Crown found it difficult to reconcile their eagerness to extract the greatest wealth of their colonies in the face of the Indians’ need to make their land to the maximum and the constant pressure of white and mestizo laborers. In the end, these excesses influenced the progressive deterioration of the social and economic conditions of indigenous communities.